Research on the mechanism of asymmetric deformation and stability control of near-fault roadway under the influence of mining. (September 2021) - Shan, Renliang; Li, Zhaolong; Wang, Chunhe; Wei, Yonghui; Bai, Yao; Zhao, Yan; Tong, Xiao
Highlights: The formula of deviator stress of circular roadway in non-uniform stress field is derived. The variation law of deviator stress and plastic zone with the size and direction of principal stress is studied. The mechanism of asymmetric deformation failure of near-fault roadway was studied. Abstract: Aiming at the asymmetrical deformation of the roadway under the influence of geological structure and mining activity, a combination of theoretical analysis, numerical simulation and field test was used to analyze the distribution of deviatoric stress and plastic zone under the condition of different stress. At the same time, the asymmetric deformation mechanism and stability control technology of the rock surrounding the near-fault roadway (NFR) were studied. The research results showed that for the surrounding rock, the size and distribution form of the deviatoric stress and the range of plastic zone were determined by the ratio K of the maximum principal stress to minimum principal stress; the deflection angle α of maximum principal stress had an effect on the orientation of the deviatoric stress concentration area and the plastic zone. As the distance d between the fault and the roadway decreased, K of the surrounding rock gradually increased, and α decreased slowly. The phenomenon of deviatoric stress concentration and the plastic failure of the surrounding rock became severe; the concentration area of deviatoric stress and the plastic zone rotated in the same direction as the principal stress. By comparing the research results with field measurements, the asymmetric deformation mechanism of NFR under the influence of mining is revealed; the fault and mining activity causes the increase and the direction deflection of the maximum principal stress of the surrounding rock, which in turn induces the deviatoric stress concentration at the far-fault roof corner and the near-fault floor corner of the roadway, and the plastic failure in the deviatoric stress concentration area. Based on the asymmetric deformation mechanism and drilling and peeping on-site, a support scheme of the arched section, in which reinforced support and shotcrete under high prestress is combined, , which can effectively control the plastic development of surrounding rock and ensure stability and safety of the roadway.